Comparison of different processing methods to prepare poly(lactid acid)–hydrotalcite composites. Issue 8 (13th August 2013) - Scaffaro, R.; Botta, L.; Passaglia, E.; Oberhauser, W.; Frediani, M.; Di Landro, L.
<x xml:space="preserve">Abstract</x> The effect of the compounding method on the morphology and on the properties of poly(lactic acid) (PLA)–hydrotalcite (HT) composites was studied. Moreover, the influence of two different kinds of HT—organically modified (OM‐HT) and unmodified (U‐HT)—and their concentration was evaluated. The composites were prepared using either a single screw extruder (SSE), a counter rotating twin‐screw compounder (TSC) or a corotating twin‐screw extruder (TSE). The prepared materials were characterized by scanning electron microscopy, gel permeation chromatography (GPC) analysis, mechanical and rheological measurements. The results indicated that the best morphology, i.e., particles dimension and distribution, is exhibited by materials prepared by TSE while the worse ones by the samples processed by SSE. The viscosity of all the materials containing the HT is lower in comparison with the viscosity exhibited by the neat matrix, in particular, when the OM‐HT is used. These results were correlated to degradation phenomena occurring during the processing of the materials as revealed by the results of GPC analysis. The addition of HT caused only a slight increase of elastic modulus of filled materials even when 5% of filler was incorporated. However, in full agreement with morphological analyses, the best performances were exhibited by materials prepared by TSE while the worse ones by the samples processed by SSE. POLYM. ENG. SCI., 54:1804–1810, 2014. © 2013 Society of Plastics Engineers